Rational speculative bubbles in the frontier emerging stock markets - M. Kabir Hassan,; Yu, Jung-Suk; Mamunur Rashid, (Penerbit Universiti Kebangsaan Malaysia, 2015)
We extend the rational speculative bubbles literature to the frontier emerging stock markets. For this purpose, this paper employs fractional integration tests and duration dependence tests based on the ARFIMA models and nonparametric smoothed hazard functions. Unlike traditional bubble tests, fractional integration tests and duration dependence tests do not show strong evidence of rational speculative bubbles in the frontier emerging stock markets.